Contraception and persecution - Rice, Charles E., 1931-2015 (St. Augustine's Press, 2014)
Contraceptive sex," wrote social science researcher Mary Eberstadt in 2012, "is the fundamental social fact of our time." In this important and pointed book, Charles E. Rice, of the Notre Dame Law School, makes the novel claim that the acceptance of contraception is a prelude to persecution. He makes the striking point that contraception is not essentially about sex. It is a First Commandment issue: Who is God? It was at the Anglican Lambeth Conference of 1930 when for the first time a Christian denomination said that contraception could ever be a moral choice. The advent of the Pill in the 1960s made the practice of contraception practically universal. This involved a massive displacement of the Divine Law as a normative measure of conduct, not only on sex but across the board. Nature abhors a vacuum. The State moved in to occupy the place formerly held by God as the ultimate moral Lawgiver. The State put itself on a collision course with religious groups and especially with the Catholic Church, which continues to insist on that traditional teacher. A case in point is the Obama Regime's Health Care Mandate, coercing employees to provide, contrary to conscience, abortifacients and contraceptives to their employees. The first chapter describes that Mandate, which the Catholic bishops have vowed not to obey. Rice goes on to show that the duty to disobey an unjust law that would compel you to violate the Divine Law does not confer a general right to pick and choose what laws you will obey. The third chapter describes the "main event," which is the bout to determine whether the United States will conform its law and culture to the homosexual (LGBTQ) lifestyle in all its respects. "The main event is well underway and LGBTQ is well ahead on points." Professor Rice follows with a clear analysis of the 2013 Supreme Court decision on same-sex marriage. Part 2 presents some "underlying causes" of the accelerating persecution of the Catholic Church. The four chapter headings in this part outline the picture: The Dictatorship of Relativism; Conscience Redefined; The Constitution: Moral Neutrality; and The Constitution: Still Taken Seriously? The answer to the last question, as you might expect, is: No. Part 3: the controversial heart of the book, presents contraception as "an unacknowledged cause" of persecution. The first chapter argues that contraception is not just a "Catholic issue." The next chapter describes the "consequences" of contraception and the treatment of women as objects. The third chapter spells out in detail the reality that contraception is a First Commandment issue and that its displacement of God as the ultimate moral authority opened the door for the State to assume that role, bringing on a persecution of the Church. The last chapter, "A Teaching Untaught," details the admitted failure of the American Catholic bishops to teach Pope Paul VI's 1968 encyclical, Humanae Vitae. But Rice offers hope that the bishops are now getting their act together Part 4: offers as a "response" to the persecution of the Church three remedies: Speak the Truth with clarity and charity; Trust God; and, most important, Pray. As the last sentence in the book puts it: "John Paul II wrote in a letter to U.S. bishops in 1993: 'America needs much prayer - lest it lose its soul.' This readable and provocative book is abundantly documented with a detailed index of names and subjects